2003
DOI: 10.1055/s-2003-45191
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of PAI-1 and tPA Activity and Thrombolytic Effects of Corilagin

Abstract: In this study, Charlton's and Tomihisa's methods were modified to investigate the thrombolytic effect of corilagin from the Chinese herbal plant Phyllanthus urinaria L., as well as its effect on carotid artery patency status. The activity of type 1 plasminogen activator inhibitor (PAI-1) in rat plasma or platelet-released substances and tissue-type plasminogen activator (tPA) in rat plasma was assayed by use of a chromogenic substrate. The results showed that corilagin had a dose-dependent thrombolytic effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…It has been shown that procyanidins and ellagitannins exert multidirectional effects on hemostasis; however, most of these studies have been conducted in vitro , which makes it difficult to predict the activity of this class of compounds after oral intake. The effect of ellagitannins on platelet activity, coagulation, and fibrinolysis was mainly studied in vitro by using plasma ( Dong et al, 1998 ), washed platelets ( Shen et al, 2003 ), and chromogenic substrates ( Zhang et al, 2004 ; Yamamoto et al, 2011 ). The effects of ellagitannin-rich products other than TE on hemostasis has also been studied in humans after oral intake.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that procyanidins and ellagitannins exert multidirectional effects on hemostasis; however, most of these studies have been conducted in vitro , which makes it difficult to predict the activity of this class of compounds after oral intake. The effect of ellagitannins on platelet activity, coagulation, and fibrinolysis was mainly studied in vitro by using plasma ( Dong et al, 1998 ), washed platelets ( Shen et al, 2003 ), and chromogenic substrates ( Zhang et al, 2004 ; Yamamoto et al, 2011 ). The effects of ellagitannin-rich products other than TE on hemostasis has also been studied in humans after oral intake.…”
Section: Introductionmentioning
confidence: 99%
“…[12]. Recent research indicated that corilagin has multiple activities including antioxidative, antiinflammatory, antiapoptotic, hepatoprotective and others.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that corilagin (ellagitannin, 7.5–60 µM) isolated from a methanolic extract obtained from the aerial parts of Phyllanthus urinaria L. (Phyllanthaceae) increased t-PA activity and decreased PAI-1 activity in plasma collected from healthy rats and also reduced the activity of PAI-1 released from thrombin-stimulated rat platelets in vitro ( Shen et al, 2003 ). The bioavailability of corilagin after oral administration to rats was 10.7% ( Zheng et al, 2016 ).…”
Section: Tannins and Fibrinolysis Systemmentioning
confidence: 99%
“…The findings of these studies indicate that the overall effect of the studied extract on thrombosis might vary depending on the pathological condition. Contrary to the P. erecta extract, corilagin injected after thrombus formation exhibited thrombolytic effect in rats which indicates its therapeutic potential ( Shen et al, 2003 ).…”
Section: Tannins and Experimental Models Of Thrombosismentioning
confidence: 99%